A Team-Teaching Approach to Advertising Campaigns Capstone Course. (May 2022) - Fernandes, Juliana; Lu, Lincoln; Nunez, Sarai
Undergraduate advertising campaigns courses are known for their integration of knowledge, application of different skills, and group work. This capstone class partners with a real-world client and may be considered the last professional experience in an educational setting before students graduate. Using a multi-methods approach, this study describes a team-teaching method developed by advertising campaigns instructors at a mid-size private university in Florida, gauges students' perceptions on several learning dimensions, and maps out how this course is taught in American universities.